Rediscovery of the 220-year-old holotype of the Banded Iguana, Brachylophus fasciatus (Brongniart, 1800) in the Paris Natural History Museum - Ineich, Ivan; Fisher, Robert N. (Zootaxa, 2016)
The Paris Natural History Museum herpetological collection (MNHN-RA) has seven historical specimens of Brachylophus spp. collected late in the 18th and early in the 19th centuries. Brachylophus fasciatus was described in 1800 by Brongniart but its type was subsequently considered as lost and never present in MNHN-RA collections. We found that 220 year old holotype among existing collections, registered without any data, and we show that it was donated to MNHN-RA from Brongniart’s private collection after his death in 1847. It was registered in the catalogue of 1851 but without any data or reference to its type status. According to the coloration (uncommon midbody saddle-like dorsal banding pattern) and morphometric data given in its original description and in the subsequent examination of the type in 1802 by Daudin and in 1805 by Brongniart we found that lost holotype in the collections. Another MNHN-RA specimen has Horn Islands (Wallis and Futuna) as the collection location but we show that most of the collections given to MNHN-RA by its collector, Louis Arnoux, have mixed localities in the MNHN-RA catalogues. We thus conclude that the locality is wrong and that the species never inhabited those islands located west of Western Samoa and north-east of Fiji.